2016
DOI: 10.1016/j.ultrasmedbio.2016.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Histotripsy Thrombolysis on Retracted Clots

Abstract: Retracted blood clots have been previously recognized to be more resistant to drug-based thrombolysis methods, even with ultrasound and microbubble enhancements. Microtripsy, a new histotripsy approach, has been investigated as a non-invasive, drug-free, and image-guided method that uses ultrasound to break up clots with improved treatment accuracy and a lower risk of vessel damage when compared to the traditional histotripsy thrombolysis approach. Unlike drug-mediated thrombolysis, which is dependent on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 61 publications
2
46
0
Order By: Relevance
“…When it is necessary to ablate a region that exceeds the electronic focal steering range, it is possible to combine electrical and mechanical focal steering in a manner similar to that developed by Zhang et al (2016) to cover the entire volume while maintaining a high ablation rate. This approach will likely prove useful for in vivo settings like abdominal targets which require a higher f-number than that used in the current study, resulting in a diminished maximum steering angle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When it is necessary to ablate a region that exceeds the electronic focal steering range, it is possible to combine electrical and mechanical focal steering in a manner similar to that developed by Zhang et al (2016) to cover the entire volume while maintaining a high ablation rate. This approach will likely prove useful for in vivo settings like abdominal targets which require a higher f-number than that used in the current study, resulting in a diminished maximum steering angle.…”
Section: Discussionmentioning
confidence: 99%
“…In these early proof of principle studies where a high treatment rate was not the primary objective, the ablation rate was a fairly modest 0.05 mL/min. In our group, Zhang et al (2016) demonstrated that histotripsy with electronic focal steering can be combined with mechanical focal steering, resulting in higher efficiency for thrombolysis applications than when mechanical steering is used alone; however, the steering range used for this application was small (± 1 mm).…”
Section: Introductionmentioning
confidence: 99%
“…However, HIFU generally carries with it the potential for damage of surrounding tissue due to diffusive heating patterns (Church 2007). While all of the aforementioned technologies have shown very promising results in the treatment of DVT, microtripsy thrombolysis hold distinct advantages over other ultrasonic thrombolysis modalities in that it is non-invasive, non-thermal, does not require injection of microbubbles or other therapeutic agents and is also effective for retracted clot (Zhang et al 2015a; Zhang et al 2015c; Zhang et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…A dual-pass strategy, previously developed in our lab (Zhang et al 2016), was used for the thrombolysis treatments in this study. The thrombus was treated with microtripsy in two passes (Figure 3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation